2020
DOI: 10.1136/jitc-2019-000478
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock and HSP70 regulate 5-FU-mediated caspase-1 activation in myeloid-derived suppressor cells and tumor growth in mice

Abstract: BackgroundWe have previously shown that 5-fluorouracil (5-FU) selectively kills myeloid-derived suppressor cells (MDSCs) and activates NLRP3 (NOD-leucine rich repeat and pyrin containing protein 3) inflammasome. NLRP3 activation leads to caspase-1 activation and production of IL-1β, which in turn favors secondary tumor growth. We decided to explore the effects of either a heat shock (HS) or the deficiency in heat shock protein (HSP) 70, previously shown to respectively inhibit or increase NLRP3 inflammasome ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In addition to DOX, previous study has found that 5-FU has an inhibitory effect on MDSCs (Pilot et al, 2020;Vincent et al, 2010). In the present study, we found that the inhibitory effect of DOX was comparable with that of 5-FU.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to DOX, previous study has found that 5-FU has an inhibitory effect on MDSCs (Pilot et al, 2020;Vincent et al, 2010). In the present study, we found that the inhibitory effect of DOX was comparable with that of 5-FU.…”
Section: Discussionsupporting
confidence: 78%
“…We previously showed that HSP70 can inhibit NLRP3 inflammasome [ 232 , 233 ]. The importance of IL-1β in tumor escape from 5-FU treatment was strengthened, with the confirmation that HSP70 deficiency in mice leads to high caspase-1 activation in MDSCs, subsequent angiogenesis, and rapid tumor growth, whereas hyperthermia (which increases HSP70 expression) inhibits these events and slows down tumor growth [ 234 ].…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…Finally, we proposed hyperthermia as a new modulator of the NLRP3 inflammasome [ 232 ]. It can block caspase-1 activation in MDSCs, and subsequent angiogenesis and rapid tumor growth in mice [ 234 ]. Although hyperthermia is already used in specific treatment protocols, further studies are required to demonstrate its efficiency in humans.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Combined with the results of this study, it is not di cult to see that TRPC6 plays an important role in the progression of glomerular disease, and taking measures against it will greatly help the diagnosis and prevention of kidney disease. NLRP3 in ammasome is one of the members of the intracellular in ammatory protein complex family, which is composed of NLRP3 protein, adaptor ASC (an apoptosis-related speck-like protein containing CARD domain) and Caspase-1 precursor 9 . In normal cells, these protein complexes exist in an inactive form.…”
Section: Discussionmentioning
confidence: 99%